Polarized Sonic Hedgehog Protein Localization and a Shift in the Expression of Region-Specific Molecules Is Associated With the Secondary Palate Development in the Veiled Chameleon - Hampl, Marek; Dumkova, Jana; Kavkova, Michaela; Dosedelova, Hana; Bryjova, Anna; Zahradnicek, Oldrich; Pyszko, Martin; Macholan, Milos; Zikmund, Tomas; Kaiser, Jozef; Buchtova, Marcela (Frontiers in Cell and Developmental Biology, 2020)
Secondary palate development is characterized by the formation of two palatal shelves on the maxillary prominences, which fuse in the midline in mammalian embryos. However, in reptilian species, such as turtles, crocodilians, and lizards, the palatal shelves of the secondary palate develop to a variable extent and morphology. While in most Squamates, the palate is widely open, crocodilians develop a fully closed secondary palate. Here, we analyzed developmental processes that underlie secondary palate formation in chameleons, where large palatal shelves extend horizontally toward the midline. The growth of the palatal shelves continued during post-hatching stages and closure of the secondary palate can be observed in several adult animals. The massive proliferation of a multilayered oral epithelium and mesenchymal cells in the dorsal part of the palatal shelves underlined the initiation of their horizontal outgrowth, and was decreased later in development. The polarized cellular localization of primary cilia and Sonic hedgehog protein was associated with horizontal growth of the palatal shelves. Moreover, the development of large palatal shelves, supported by the pterygoid and palatine bones, was coupled with the shift in Meox2, Msx1, and Pax9 gene expression along the rostro-caudal axis. In conclusion, our results revealed distinctive developmental processes that contribute to the expansion and closure of the secondary palate in chameleons and highlighted divergences in palate formation across amniote species.